Intellectual Property Rights, the Industrial Revolution, and the Beginnings of Modern Economic Growth - Mokyr, Joel (American Economic Review, 2009)
There is a growing consensus that in all cases of successful and unsuccessful economic growth, institutions mattered (Elhanan Helpman